New Amino Naphthoquinone Derivatives as Anti-Trypanosoma cruzi Agents Targeting Trypanothione Reductase - Christian Espinosa-Bustos; Mariana Ortiz Pérez; Alonzo Gonzalez-Gonzalez; Ana María Zarate; Gildardo Rivera; Javier A. Belmont-Díaz; Emma Saavedra; Mauricio A. Cuellar; Karina Vázquez; Cristian O. Salas (MDPI AG, 2022)
To develop novel chemotherapeutic alternatives for the treatment of Chagas disease, in this study, a set of new amino naphthoquinone derivatives were synthesised and evaluated in vitro on the epimastigote and trypomastigote forms of Trypanosoma cruzi strains (NINOA and INC-5) and on J774 murine macrophages. The design of the new naphthoquinone derivatives considered the incorporation of nitrogenous fragments with different substitution patterns present in compounds with activity on T. cruzi, and, thus, 19 compounds were synthesised in a simple manner. Compounds 2e and 7j showed the lowest IC50 values (0.43 µM against both strains for 2e and 0.19 µM and 0.92 µM for 7j). Likewise, 7j was more potent than the reference drug, benznidazole, and was more selective on epimastigotes. To postulate a possible mechanism of action, molecular docking studies were performed on T. cruzi trypanothione reductase (TcTR), specifically at a site in the dimer interface, which is a binding site for this type of naphthoquinone. Interestingly, 7j was one of the compounds that showed the best interaction profile on the enzyme; therefore, 7j was evaluated on TR, which behaved as a non-competitive inhibitor. Finally, 7j was predicted to have a good pharmacokinetic profile for oral administration. Thus, the naphthoquinone nucleus should be considered in the search for new trypanocidal agents based on our hit 7j.